Photoluminescence studies of the formation of MgS/CdSe quantum dots grown by molecular beam epitaxy - Funato, M; Bradford, C; Balocchi, A; Smith, J; Prior, K; Cavenett, B (2002)
The optical properties of MgS/CdSe quantum structures grown by molecular beam epitaxy are characterized by photoluminescence (PL) spectroscopy. The increase in the CdSe thickness from 1 to beyond 3 monolayers results in the formation of, at first, quantum wells (QWs) and then quantum dots (QDs) by Stranski-Krastanov growth. The PL temperature dependence measurements show clear difference in the optical properties of QWs and QDs.